Pengaruh Harga, Promosi, Dan Kualitas Pelayanan Terhadap Loyalitas Wali Siswa Pada Homeschooling Bina Mandiri Di Kota Batam - Dabur, Feliks; Sihaloho, Asner (Tractare: Jurnal Ekonomi-Manajemen, 2023)
The purpose of this study was to determine the effect of price, promotion and service quality on the loyalty of student guardians at Bina Mandiri Homeschooling in Batam City.The sample used in this study was 100 respondents from 137 parents who were randomly selected. The method used in this study is a simple random sample method. The data analysis method used is Test Validity, Reliability, Normality, Multicollinearity, and Multiple Regression Analysis. The correlation between price, promotion and service quality has a fairly strong relationship, namely 46.40%. Proving the hypothesis obtained t test results on the price variable with tcount -1.875 < ttable 1.984, promotion variable with tcount 3.212 > ttable 1.984, and service quality variable tcount 7.139 > ttable 1.984 Based on the F Test the results obtained Fcount 29.568 > Ftable 3.090. The results of this study indicate that price has a negative effect on the loyalty of student guardians, promotion has a positive effect on student guardian loyalty, service quality has a positive effect on student guardian loyalty. Price, promotion and quality of service together have a positive and significant effect on the loyalty of guardians of Bina Mandiri Homeschooling students in Batam City.